The Influence of Service Failure on Mobile Banking Usage and Its Relation to User Satisfaction - Ovio Destiana Sugiono; Citra Kusuma Dewi; Putu Nina Madiawati (Journal of The Community Development in Asia, 2025)
The explosive expansion of the internet has changed the way banks communicate with their clients. MyBCA, a mobile banking (m-banking) application, is designed to meet the needs of customers who prefer banking from home. This study aims to analyze the impact of m-banking service failures on MyBCA user adoption and satisfaction. 390 respondents participated in this quantitative study, with data analysis using SMARTPLS 3.1. Results show that m-banking adoption is significantly affected by functional, system, information, and service failures. In addition, the use of m-banking was also found to have a significant influence on use satisfaction towards m-banking. Despite functional failures, users still use m-banking frequently. System failures, such as technical glitches, have a significant impact on usage. In contrast, information failures have less impact than other failures. Service failures, such as transaction errors, also have a major impact on usage. This study uses MBFM to analyze the interrelationships between service failures, m-banking adoption, and user satisfaction, providing important insights for the future development of m-banking services. The results of this study can be used as a basis for designing more targeted service quality improvement strategies, with a priority on improving the core features that are most frequently used by users